Effects of dietary addition of mulberry leaf powder on blood metabolites and fecal microbiota composition in Hu sheep - Guo, Liangyong; Shi, Xingyun; Cao, Fang; Hu, Shilei; Qian, Wenchun (Frontiers in Animal Science, 2025)
In livestock production, ruminant feed resources are often scarce, and numerous challenges arise during production, such as immune disorders and oxidative stress. Mulberry leaves are rich in various nutrients and exhibit significant antioxidant and immune-regulating properties. Therefore, they can be used as an unconventional feed resource in livestock production. This study investigated the effects of mulberry leaves (ML) as a feed supplement on the blood biochemical parameters and hindgut microbial structure of Hu sheep. Sixteen Hu sheep were randomly divided into two groups and fed either 0 or 60 g/d of ML. Compared to the control group, sheep fed ML showed a significant increase in AKP (P = 0.027) and GPT (P = 0.002) levels in the blood, while TP (P = 0.001) levels decreased significantly. Additionally, there was an increasing trend in GSH-Px (P = 0.082) and CAT (P = 0.058) levels. After the addition of ML, the abundance of Campylobacterota, Campylobacter, and Mailhella in the hindgut significantly increased (P < 0.05), while the abundance of Alloprevotella, Roseburia, and Prevotellaceae UCG-003 significantly decreased (P < 0.05). Therefore, ML can serve as a natural feed supplement to regulate the immune status of animals, thereby promoting the healthy production of ruminants.